Automated calibration for optical see-through head mounted display using display screen space based eye tracking - Tomi, A.B. (Institute of Electrical and Electronics Engineers Inc., 2016)
A crucial problem in Augmented Reality (AR) applications that used optical see-through head mounted display (OST HMD) is frequent (re)calibrations. It is considered time consuming and distract users from their application if each such frequent (re)calibrations involve user interactions. Furthermore, it will be prone to user-dependent errors into the system setup thus leads to reduce user's acceptance on OST HMD in AR applications. Nowadays, a few studies toward interaction-free calibration implementation on OST HMD have been done. Recent implementation on interaction-free calibration issues are associated with the virtual display calibration which is related to the eye and world camera relation with display screen. Thus, we propose a novel approach that utilizes a display screen space based eye tracking into OST HMD calibration. By simultaneously measuring eye movements and map the tracked eye coordinate into a 2D display screen space, a calibration formulation can be done without involving the eye tracker properties. This work is expected to be established for efficient and high accuracy interaction-free OST HMD calibration which will be beneficial in AR applications that used OST HMD. Â© 2016 IEEE.